An Insight into the Role of Glycerol in Chitosan Films - Rivero, Sandra (2016)
This work was focused on assessing the influence of the glycerol in chitosan matrices, analyzing the changes produced in the molecular mobility, mechanical, thermal, barrier and structural properties. The addition of glycerol in the matrix decreased the stress values, increasing the elasticity and water vapor permeability of the films, with a marked decrease in glass transition temperature; Detailed analyses of Fourier Transform IR Spectroscopy spectra supported the observed changes, especially in the spectral windows 1700– 1500 cm−1 revealing the modifications at molecular level caused by hydrogen bond interactions between chitosan and water in the presence of glycerol. Positron annihilation spectroscopic (PALS) measurements allowed determining the free volume assuming spherical holes as well as monitoring the structural changes in chitosan films caused by the addition of both, glycerol and water molecules. It was possible to infer that for unplasticized matrices, a sustained increase of the radius between 0.06 and 0.2 of Xwater was observed, followed by a plateau up to 0.35. In the other case, with the addition of glycerol, there were two plateaus, the first between 0.25 and 0.37 of Xwater, and the second from 0.41 to 0.47. For higher glycerol concentrations, the plasticizer would be mainly bounded to the chitosan pack more efficiently and the water present in the system would be predominantly free in the matrix causing its swelling. Findings on molecular mobility contributed to the understanding of the role of water and glycerol in the structural arrangement and its influence on film properties.